A Systematic Review and Meta-Analysis on Microsurgical Safety and Efficacy of Profunda Artery Perforator Flap in Breast Reconstruction. (29th July 2019) - Qian, Bei; Xiong, Lingyun; Li, Jialun; Sun, Yang; Sun, Jiaming; Guo, Nengqiang; Wang, Zhenxing
Abstract : Background . The profunda artery perforator (PAP) flap was first applied in breast reconstruction in 2010 by Robert J. Allen. It provided an alternative for autologous breast reconstruction in addition to traditional donor sites. Currently, literature reporting its microsurgical safety and efficacy is relatively sparse and heterogeneous . Objective . To clarify the evidence regarding microsurgical safety and efficacy of PAP flap in breast reconstruction, which may contribute to future surgical decision-making. Methods . Multiple databases were systematically searched by two independent reviewers. The result was statistically analyzed with Meta command of R GUI 3.5.1. The proportions with 95% confidence intervals (CIs) were calculated by using random-effect model. Results . There were 12 studies including 516 PAP flaps meeting the inclusion criteria. The pooled surgical success rate was 99% (95% CI: 97%–100%) and overall rate of complications was 23% (95% CI: 18%–27%). The most common individual complication was wound dehiscence with incidence of 6% (95% CI: 4%–9%). The seroma rate was 2% (95%CI: 0%–6%). The hematoma rate was 1% (95% CI: 0%–2%). The partial necrosis rate was 2% (95% CI: 0%–5%). The rate of total flap loss was 1% (95% CI: 0%–3%). Conclusion . To date, this study is the first meta-analysis of microsurgical efficacy and safety evaluation of the PAP flap in breast reconstruction. This present work confirmed that the PAP flap is safe and reliable in breast reconstruction with high success rate, but a relatively low complication rate. Moreover, it might be more than an alternative to the deep inferior epigastric perforator flap (DIEP) in microsurgical breast reconstruction in selected patients.